2006
DOI: 10.1002/chin.200637016
|View full text |Cite
|
Sign up to set email alerts
|

Plasma Processing Approach to Molecular Surface Tailoring of Nanoparticles: Improved Photocatalytic Activity of TiO2.

Abstract: ChemInform is a weekly Abstracting Service, delivering concise information at a glance that was extracted from about 200 leading journals. To access a ChemInform Abstract, please click on HTML or PDF.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
6
0

Year Published

2007
2007
2012
2012

Publication Types

Select...
3

Relationship

2
1

Authors

Journals

citations
Cited by 3 publications
(6 citation statements)
references
References 1 publication
0
6
0
Order By: Relevance
“…A home-built custom reactor, capable of continuous 3608 rotation during the plasma deposition, was employed to overcome the tendency for particle aggregation and thus promote more uniform polymer film coverage of the substrates. 37,38 One gram samples of the particles were coated in each run. The polypropylene microspheres were soaked in ethanol, followed by prolonged vacuum drying prior to the plasma treatment.…”
Section: Modification Of Polymeric Surfacesmentioning
confidence: 99%
See 1 more Smart Citation
“…A home-built custom reactor, capable of continuous 3608 rotation during the plasma deposition, was employed to overcome the tendency for particle aggregation and thus promote more uniform polymer film coverage of the substrates. 37,38 One gram samples of the particles were coated in each run. The polypropylene microspheres were soaked in ethanol, followed by prolonged vacuum drying prior to the plasma treatment.…”
Section: Modification Of Polymeric Surfacesmentioning
confidence: 99%
“…Our laboratory has recently developed a modified Radio Frequency Glow Discharge (RFGD) technique to functionalize a wide variety of micro, 37 and more recently, nanosized, spheres. 38 Additionally, using a pulsed plasma technique, we have previously shown that we can effectively control the film chemistry obtained from a given monomer undergoing polymerization via simple variations in the plasma duty cycles employed. This film chemistry control can be used to permit retention of normally reactive functional groups in monomers polymerized under plasma conditions 39,40 and this technology has been successfully employed in a variety of biomaterial applications.…”
mentioning
confidence: 99%
“…Furthermore, the plasma deposit forms a pinhole-free, conformal film over the substrate. Plasma polymerisation has been successfully applied to substrates such as 3D scaffolds [22] and microparticles [23]. Gradients of chemical functionality have also been fabricated using this method [24] and can be tailored for investigations into cell behaviour [16,25].…”
Section: Introductionmentioning
confidence: 99%
“…These prior investigations have included doping TiO 2 with transition metals such as Ni, Fe, Cu or Mn to broaden light absorption into the visible region and decrease the rate of recombination between exited electrons and holes. TiO 2 has also been doped by a variety of other materials including carbon, nitrogen, sulfur, fluorine, and tetramethyltin …”
Section: Introductionmentioning
confidence: 99%
“…The use of plasma processing to modify TiO 2 catalytic activity has been reported in several recent studies. These studies include use of a nitrogen discharge to produce N-doped TiO 2 , acrylic acid to deposit an amorphous polymer coating on TiO 2 , and plasma deposition of a tin containing coating on TiO 2 which was subsequently converted to tin oxide by calcination . In all three cases appreciable increases in TiO 2 photocatalytic activity were reported.…”
Section: Introductionmentioning
confidence: 99%